2016
DOI: 10.1007/s00198-016-3623-6
|View full text |Cite
|
Sign up to set email alerts
|

GRAND-4: the German retrospective analysis of long-term persistence in women with osteoporosis treated with bisphosphonates or denosumab

Abstract: SummaryThis retrospective database study assessed 2-year persistence with bisphosphonates or denosumab in a large German cohort of women with a first-time prescription for osteoporosis treatment. Compared with intravenous or oral bisphosphonates, 2-year persistence was 1.5–2 times higher and risk of discontinuation was significantly lower (P < 0.0001) with denosumab.IntroductionPersistence with osteoporosis therapies is critical for fracture risk reduction. Detailed data on long-term persistence (≥2 years) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 40 publications
2
33
0
5
Order By: Relevance
“…Previous persistence studies of denosumab covering the USA, Canada and several European countries excluding the UK have reported persistence at 12 months of 55.9-99.1% and at 24 months of 34.8-99.5% [24][25][26][27][28][29][30][31][32][33][34][35]. In contrast, for other parenteral therapies, the previous studies reported persistence at 12 months of 33.8-74.5%, and for oral therapies reported 10-78% [21,28].…”
Section: Discussionmentioning
confidence: 94%
“…Previous persistence studies of denosumab covering the USA, Canada and several European countries excluding the UK have reported persistence at 12 months of 55.9-99.1% and at 24 months of 34.8-99.5% [24][25][26][27][28][29][30][31][32][33][34][35]. In contrast, for other parenteral therapies, the previous studies reported persistence at 12 months of 33.8-74.5%, and for oral therapies reported 10-78% [21,28].…”
Section: Discussionmentioning
confidence: 94%
“…In German and Swedish studies, persistence with denosumab was substantially higher than that seen with intravenous or oral bisphosphonates [13, 14]; in a Hungarian study, persistence was considerably lower with daily, weekly, and monthly treatments (10–18%) than with 6-monthly denosumab [15]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that younger age, specifically individuals less than 60 years old versus older age, is associated with lower persistence and adherence [13, 16, 18, 19]. While one study found no association between age and persistence [14], others have reported older age to be associated with lower persistence [17].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis showed no significant difference in safety and reduction of fracture risk between denosumab and bisphosphonate therapy although higher gains in BMD were obtained with denosumab [44]. More advantages of denosumab are the safety of the drug in patients with renal insufficiency and the lower risk of discontinuation [45]. Effects of denosumab up to 8 years of treatment are promising with continuing gains in BMD [46].…”
Section: Advances In Prevention or Treatment Of Glucocorticoid-inducementioning
confidence: 99%